Associations between dietary patterns at age 71 and the prevalence of sarcopenia 16 years later. Issue 4 (April 2020) - Karlsson, Mikael; Becker, Wulf; Michaëlsson, Karl; Cederholm, Tommy; Sjögren, Per
Summary: Background & aims: The growing recognition of the significance of sarcopenia has highlighted the need to understand etiologic factors, where food intake likely plays a role. The aim was to investigate the association between dietary patterns at mean age 71 and the prevalence of sarcopenia at mean age 87 in a Swedish cohort of community dwelling men. Methods: Dietary habits were assessed using a 7-day food record. Adherences to official dietary guidelines, defined by the World Health Organization (WHO) by using the Healthy Diet Indicator, and Mediterranean-like dietary habits by using the Mediterranean Diet Score, were calculated. Sarcopenia was determined using the definition from the European Working Group on Sarcopenia in Older People (EWGSOP) and associations to each dietary pattern were analyzed using logistic regression, adjusted for potential confounders. Results: Our study population included 254 men, mean age 71 at baseline, and 53 (21%) were defined as sarcopenic 16 years later. There was no linear relationship between increased adherence to WHO dietary guidelines and future prevalence of sarcopenia, although those with medium adherence seemed to be protected (crude OR = 0.41, 95% CI 0.19–0.92). On the other hand, an inverse relationship to sarcopenia was found for each SD increment in the Mediterranean diet score (crude OR = 0.68, 95% CI 0.46–0.99), which remained after adjusting for potential confounders. Sensitivity analysis indicated relationships to be independent of changes in physical activity and dietary misreporting. Conclusions: In this prospective study of elderly men, using a single measure of diet at age 71 as a reflection of habitual dietary habits, healthy dietary patterns tended to protect against the development of sarcopenia over 16 years. In particular, we found indications that increased adherence to a Mediterranean dietary pattern might be advantageous.